Clinical and radiological characteristics of pediatric COVID-19 before and after the Omicron outbreak: a multi-center study - Lin, Bin; Xu, Xiaopei; Shen, Zhujing; Huang, Peiyu; Gao, Yuantong; Liu, Jun; Xie, Zongyu; Zhao, Tongtong; Xia, Junli; Lv, Jian; Ren, Dawei; Zheng, Hanpeng; et al. (Frontiers in Pediatrics, 2023)
We aimed to compare the clinical and radiological features of pediatric COVID-19 patients in the early phase of the pandemic and during the Omicron outbreak. We retrospectively analyzed 68 pediatric patients with COVID-19, including 31 infected with the original strain of SARS-CoV-2 in the early phase (original group), and 37 infected with the Omicron strain during the Omicron outbreak (Omicron group). Clinical symptoms and chest CT images were analyzed for each patient to evaluate clinical characteristics, and the extent and severity of lung involvement. We found that the chest CT findings of pediatric COVID-19 patients were mostly normal or mild, while the Omicron group had a significantly lower CT severity score than the original group.Ground-glass opacities were the most common radiological findings in both phases. In addition, we observed that children in the Omicron group had fewer symptoms, milder clinical manifestations, and faster recovery than those in the original group. We conclude that the clinical and radiological characteristics of pediatric COVID-19 patients have changed with the emergence of the Omicron variant. When CT examinations are needed in children with severe clinical symptoms, it is important to consider the effects of ionizing radiation on them and to use individualized scanning protocols and protection strategies. Our findings provide insights into the changes in the disease spectrum and can aid in the diagnosis and treatment of pediatric COVID-19 patients.